2018
DOI: 10.1017/ice.2018.236
|View full text |Cite
|
Sign up to set email alerts
|

How frequently are hospitalized patients colonized with carbapenem-resistant Enterobacteriaceae (CRE) already on contact precautions for other indications?

Abstract: Using samples collected for VRE surveillance, we evaluated unit-admission prevalence of CRE perirectal colonization and whether CRE carriers (unknown to staff) were on contact precautions for other indications. CRE colonization at unit-admission was infrequent (3.9%). Most CRE carriers were not on contact precautions, representing a reservoir for healthcare-associated CRE transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…Risk factors for CRE colonization are numerous. Previous studies reported that severe underlying diseases, previous ICU hospitalization, long hospital stay, more invasive procedures, recent surgical history, previous infection history, long-term antibiotic use, long-term glucocorticoid use, and undergoing a transplant were risk factors for CRE colonization [15,[26][27][28][29]. However, in our study, no statistical signi cance in terms of the history of ICU hospitalization, invasive procedures, and steroid use between colonization and the non-colonization groups was found.…”
Section: Discussioncontrasting
confidence: 84%
“…Risk factors for CRE colonization are numerous. Previous studies reported that severe underlying diseases, previous ICU hospitalization, long hospital stay, more invasive procedures, recent surgical history, previous infection history, long-term antibiotic use, long-term glucocorticoid use, and undergoing a transplant were risk factors for CRE colonization [15,[26][27][28][29]. However, in our study, no statistical signi cance in terms of the history of ICU hospitalization, invasive procedures, and steroid use between colonization and the non-colonization groups was found.…”
Section: Discussioncontrasting
confidence: 84%
“…29 Consistent with the previous reports, CRE colonization in patients from community settings was infrequent. Healthcare facilities are usually considered as reservoirs of transmission 30 of CRE, and the healthcare providers are partly to blame in CRE acquisition among hospitalized patients. 31 Moreover, antibiotic exposures and invasive practices such as mechanical ventilation, percutaneous intervention and surgery increase the probability of CRE colonization and infection, 32,33 and more than half CRE colonizers had such experiences before CRE being detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…As clinical cultures alone identify only a fraction of CRE patients [5], the majority of unrecognized CRE patients, a potential source of CRE transmission, might not be following contact precautions [1]. However, as a limited application of AST may increase the risk of missing unrecognized CRE patients, early detection of patients at high risk of CRE acquisition at hospital unit admission has been emphasized [6]. A few studies have identified the risk factors of model to assess the patients at high risk of CRE acquisition [7e9].…”
Section: Introductionmentioning
confidence: 99%